Sintomas vocais referidos e videolaringoscopia de docentes da educação básica - Brito, Alessandra Regina (2015)
The teaching profession is one that have a higher incidence of changes and vocal symptoms. This thesis built on the model of scientific articles, features sociodemographic profile of Basic Education teachers and examines associations between vocal symptoms reported in perception protocols, with videolaryngoscopy. Descriptive, cross-sectional study with 107 female teachers, active in seven public schools in Goiânia. The theme of the literature review investigated using the teaching descriptors, voice, dysphonia, vocal cord dysfunction and video laryngoscopy, in the databases PubMed, LILACS, SciELO included studies in English and Portuguese, in the period 2001-2015. Of the 174 publications found, 135 were excluded and 17 were part of the integrative review. Among the symptoms reported, hoarseness was the most cited and the examination videolaryngoscopy, the most widely used, but the exams analysis parameters, were not unanimous. Among the laryngeal disorders, they stood out glottal slit, nodules and laryngopharyngeal reflux. The second article presents the results of research, including sociodemographic profile and the association of self-perception of vocal symptoms reported by teachers, with the analyzes of videolaryngoscopy. The instruments were questionnaire and protocols Voice Disorder Screening Index, Profile Participation and Activities Vocals and videolaryngoscopy record. There was aged predominantly between 40 and 49 years, and 72 (67%) worked in elementary school, 23 (21%) Education Infant and Nursery, 12 (11%) in Special Education. For the working time 33 (31%) teach between 1-10 years, 46 (43%) of 11-20 years and 28 (26%) over 20 years. With regard to the shift, 56 (52%) in a working period, 46 (43%) in two and 5 (5%) for over two periods or shifts. The prevalence of teachers with vocal symptoms reported 82 (77%) and 44 (41%) with laryngeal changes to videolaryngoscopy. Data were described by bivariate analysis and odds ratios finding significance between hoarseness symptoms (p = 0.005), loss of voice (p = 0.042), and breaks in the voice (p = 0.002). On examination videolaryngoscopic, 19 (18%) teachers showed signs of laryngopharyngeal reflux, 16 (15%) nodules, 5 (5%) and slot 4 (4%) vocal fold polyps associated with symptoms of hoarseness, loss of voice and breaks voice (p <0.05). There was significance between hoarseness symptoms (p = 0.005), loss of voice (p = 0.042), and breaks in the voice (p = 0.002) compared to videolaryngoscopic findings. Vocal fatigue (21%) was the most vocal symptom referred by teachers. There was no significant association between the sociodemographic data and laryngeal alterations found in videolaryngoscopy. Conclusion: In the literature review, there were no publications that associate the protocols Voice Disorder Screening Index (IDTV) and Profile Participation and Voice Activity (VAPP) to take videolaringoscopia.Este study revealed a significant association between vocal symptoms hoarseness, loss of voice and breaks the voice raised by teachers with laryngeal alterations found in videolaryngoscopy. However, teachers were identified with symptoms and changes to videolaryngoscopy, as well as teachers with symptoms and without changes to the exam and teachers without symptoms, but with examination of changes laryngoscopy, as well as limitations and restrictions in daily activities, in the presence of voice disorders .